(3QDhS GdbhGQjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3EfJNHJ gPG hbO bSeJg CQHYI CHhGH GdHGH GdChd ai PcQ GdeNJGQ ef GdNWH s
(3BNQgG (B:s
(3eG CYLdg jGdSaQc eG CWhdg jG dWQjbc eG Cghdg jGdYbdc NjQ efg GdHdg BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eLGdS YdejIs
(3HBNQg JUMjMGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs